Association Between Factors Involved in Bone Remodeling (Osteoactivin and OPG) With Plasma Levels of Irisin and Meteorin-Like Protein in People With T2D and Obesity - Cherian, Preethi; Al-Khairi, Irina; Jamal, Mohammad; Al-Sabah, Suleiman; Ali, Hamad; Dsouza, Carol; Alshawaf, Eman; Al-Ali, Waleed; Al-Khaledi, Ghanim; Al-Mulla, Fahd; Abu-Farha, Mohamed; Abubaker, Jehad (Frontiers in Endocrinology, 2021)
The musculoskeletal system consisting of bones and muscles have been recognized as endocrine organs secreting hormones that are involved in regulating metabolic and inflammatory pathways. Obesity and type 2 diabetes (T2D) are associated with several musculoskeletal system complications. We hypothesized that an interaction exists between adipomyokines namely, irisin and METRNL, and various molecules involved in bone remodeling in individuals with obesity and T2D. A total of 228 individuals were enrolled in this study, including 124 non-diabetic (ND) and 104 T2D. A Multiplex assay was used to assess the level of various osteogenic molecules namely osteoactivin, Syndecan, osteoprotegerin (OPG) and osteonectin/SPARC. Our data shows elevated levels of Osteoactivin, Syndecan, OPG and SPARC in T2D as compared to ND individuals (p ≤ 0.05). Using Spearman’s correlation, a positive correlation was observed between irisin and Osteoactivin as well as OPG (p < 0.05). Similarly, a positive association was observed between METRNL and Osteoactivin (p < 0.05). The strong positive association shown in this study between irisin, METRNL and various molecules with osteogenic properties emphasize a possible interaction between these organs. This report suggests that having a dysregulation in the level of the aforementioned molecules could potentially affect the development of bone and muscle related complications that are associated with obesity and T2D.